Effect of design parameters of dental implant on stress distribution: a finite element analysis - Rahmanivahid, Pooyan; Heidari, Milad (International Journal of Engineering and Technology, 2020)
Nowadays, root osseointegrated dental implants are used widely in dentistry mainly for replacement of the single missing tooth. The success rate of osseointegrated dental implants depends on different factors such as bone conditions; surgery insertion technique, loading history, and biomechanical interaction between jawbone and implant surface. In recent years, many studies have investigated design factors using finite element analysis with a concentration on major parameters such as diameter, pitch, and implant outlines in the distribution of stress in the bone-implant interface. There is still a need to understand the relationship and interaction of design factors individually with stress distribution to optimize implant structure. Therefore, the present study introduced a new dental implant and investigated the effect of design parameters on stress distribution. The finite element modeling was developed to facilitate the study with a comparison of design parameters. Boundary and loading conditions were implemented to simulate the natural situation of occlusal forces. Based on results, V-shape threads with maximum apex angle caused a high rate of micro-motion and high possibility of bone fracture. Low Von-Mises stress was associated with low bone growth stimulation. Besides, small fin threads did not integrate with cancellous bone and consequently lower stress accommodation. V-5 fin had no extraordinary performance in cancellous bone. Small surface areas of fins did not integrate with the surrounding bone and high-stress concentration occurred at the tail. These fins are recommended as threads replacement. It was concluded that the implant structure had less influence on stress distribution under horizontal loading.Â Â